Pengaruh Kualitas Pelayanan, Servicescape dan Harga Terhadap Kepuasan Konsumen - Vina Islami (Universitas Bina Sarana Informatika, 2019)
Globalization now has a big impact on people's lives, especially seen from their lifestyle. The mindset of a developing and changing society does not escape the influence of technological progress. Facing competition, companies must be able to place their products in the midst of intense business competition. Consumers today are smarter and selective in choosing the goods and services used. This study aims to examine the effect of service quality, servicescape, and prices on consumer satisfaction at consumers of Jasmine Beauty Clinic Bogor.This study used a survey research design on respondents by distributing questionnaires to consumers of Jasmine Beauty Clinic Bogor. The population of this study was the Bogor community who took care at Jasmine Beauty Clinic Bogor. The sample in this study amounted to 120 respondents using a purposive sampling technique with the criteria of respondents having done treatment at Jasmine Beauty Clinic Bogor and aged over 17 years. The data collection technique uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. Data analysis using multiple linear regression and hypothesis testing using the partial significance test (t test).The results of multiple linear regression analysis with SPSS version 16 show that service quality, servicescape, and prices partially have a positive and significant effect on customer satisfaction. Keywords: service quality, servicescape, price and customer satisfaction.